Preparation of spherical FeSiCr powders by improved combination atomization process - CUI Lei; MA Hongqiu; ZHAO Gang; MENG Lingbing; GUAN Lidong; FENG Xuefeng (Fenmo yejin jishu)
The conventional combined atomization smelting process was improved and optimized in this paper, the powder morphology was improved by enhancing the effect of the primary atomization stage and prolonging the time of droplet spheroidization. Spherical powders with different particle sizes were prepared by the improved combination atomization process and compared with those prepared by the conventional combination atomization. The results show that the powders prepared by the improved atomization process show the characteristics as good morphology, small specific surface area, and low oxygen content. At the same time, the permeability is lower than that of the conventional atomized powders, but the DC bias ability of magnetic core is significantly improved, and the hysteresis loss and eddy current loss are significantly reduced.